The triumph of provocation - Mackiewicz, Józef. (New Haven : Yale University Press, 2009)
This political treatise examines the history and nature of Communism as it developed in the Soviet Union and in Poland. The author argues that accommodation with the Communists simply helped them to impose their vision of the world and pursue their goal of global domination.
"Censored" -- Does Russia still exist? -- Between Bolshevism and nationalism -- Mikaszewicze -- "Gomułkaism" (national communism) of the twenties -- The first great provocation about the alleged "evolution of communism" -- The second phase of national communism -- Alliance or collaboration with the Soviet invader? -- The origins of "PAX" -- Pharisaism versus subversion -- The second great provocation -- Along the road of classic "Poputnichestvo" (fellow-traveling) -- The German complex -- Culture in the stranglehold of compulsory infantilism -- The real German threat -- "Realisms" versus reality -- Pathos versus pestilence -- Józef Mackiewicz : his life, work, and views (a chronology) / by Nina Karsov.
Includes bibliographical references.
Print version record.
Transl. from the Polish.
eBooks on EBSCOhost
Keywords: Mackiewicz, Józef.; Mackiewicz, Józef; Communism -- Poland; Poland -- Relations -- Soviet Union; Soviet Union -- Relations -- Poland; Poland -- Politics and government -- 1945-1980.; Pologne -- Politique et gouvernement -- 1945-1981.; POLITICAL SCIENCE -- Government -- International; POLITICAL SCIENCE -- International Relations -- General; HISTORY -- General; Communism; International relations; Politics and government; Poland; Soviet Union; Communism -- Politics and Government. -- Poland; 1945-1980